Modeling and Solving Fractional Differential Algebraic Equations in Smart Control Systems - Khalid Farhan FazeaA (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
In this have a look at, a new mathematical model for FDAE-based smart manage systems is proposed. The model carries fractional derivatives blended with algebraic constraints to symbolize prolonged memory results. We describe a numerical method to solve the proposed device and practice this version to robotics, self-reliant cars, and sensible prosthetics. The Fractional Collocation Method is employed to resolve FDAEs, making sure accuracy and balance. To validate the proposed method, we introduce 3 examples: a simple FDAE demonstrating the accuracy of the numerical solution, a device of FDAEs modeling interdependent dynamic variables with algebraic constraints, and an FDAE with a nonlinear algebraic constraint, highlighting the approach's capability to handle complicated, nonlinear dynamics. Simulation results verify that FDAEs offer a more practical and powerful tool for designing and reading wise manage systems as compared to classical techniques.